Immune-Mediated Bidirectional Causality Between Inflammatory Bowel Disease and Chronic Periodontitis: Evidence from Mendelian Randomization and Integrative Bioinformatics Analysis - Zhijun Feng; Zihan Chen; Xiaoxu Wang; Meijuan Zhou; Shupeng Liu (Biomedicines)
Background/Objectives: A bidirectional association between inflammatory bowel disease (IBD) and periodontitis has been observed, yet their causal relationship remains unclear. This study aimed to investigate the potential causal links between these two inflammatory conditions through comprehensive genetic and molecular analyses. Methods: We conducted a bidirectional Mendelian randomization (MR) analysis integrated with bioinformatics approaches. The causal relationships were primarily evaluated using inverse variance weighting (IVW), complemented by multiple sensitivity analyses to assess the robustness of the findings. Additionally, we performed differential gene expression analysis using RNA sequencing data to identify co-expressed genes and shared inflammatory mediators between IBD and periodontitis, followed by pathway enrichment analysis. Results: Bidirectional MR analysis revealed significant causal associations between IBD and periodontitis (p-value < 0.05). Sensitivity analyses demonstrated the consistency of these findings, with no evidence of significant heterogeneity or horizontal pleiotropy (p-value > 0.05). Integrated bioinformatics analysis identified key immune regulators, particularly interleukin 1 beta (IL1B) and C-X-C motif chemokine receptor 4 (CXCR4), and inflammatory signaling pathways, including tumor necrosis factor (TNF-α) and interleukin 17 (IL17), as potential molecular mechanisms underlying the bidirectional relationship between these conditions. Conclusions: Our findings provide genetic evidence supporting a bidirectional causal relationship between IBD and periodontitis. Transcriptomic analysis revealed shared pathological mechanisms and identified crucial immune regulatory factors common to both diseases. These insights enhance our understanding of the molecular interplay between IBD and periodontitis, potentially informing new therapeutic strategies for both conditions.